Rodents of the subfamily Sigmodontinae (Myomorpha: Cricetidae) as hosts for South American hard ticks (Acari: Ixodidae) with hypotheses on life history - Guglielmone, Alberto Alejandro (2011)
Historical information shows that Sigmodontinae are irrelevant hosts for South American ticks of the genera Haemaphysalis Koch, Rhipicephalus Koch and Dermacentor Koch. Nine Amblyomma Koch species were found on Sigmodontinae but only Amblyomma triste Koch, 1844 appears strongly related to them. Eighteen species of Ixodes Latreille were determined on these hosts. Four species sporadically infest Sigmodontinae; eight are found mostly on Sigmodontinae but the records are too few for any inference. Six: I. amarali Fonseca, 1935, I. longiscutatus Boero, 1944, I. loricatus Neumann, 1899, I. luciae Sénevet, 1940, Ixodes sigelos Keirans, Clifford and Corwin, 1976 and I. venezuelensis Kohls, 1953 are usual parasites of Sigmodontinae. It is proposed that the Ixodes-Sigmodontinae relationship evolved from a South American tick ancestor parasite of Didelphidae. Their descendants are two extant clades, one formed by I. loricatus-I. luciae defined by analysis of 16S rDNA sequences further including I. amarali and I. schulzei by morphological affinities. These species (I. schulzei excluded) have adult ticks feeding on Didelphidae and sub-adult ticks feeding on Didelphidae and several species from five sigmodontin tribes. The second clade is formed by I. abrocomae Lahille, 1916 (known from few specimens, mostly collected from Sigmodontinae), I. sigelos (mainly a parasite of Sigmodontinae), I. stilesi Neumann, 1911 (parasite of deer), and possibly I. taglei Kohls, 1969 (parasite of deer) by morphological affinity. This clade is related to I. neuquenensis Ringuelet, 1947, an exclusive parasite of Dromiciops gliroides Thomas (Microbiotheriidae Ameghino).